The Management of Pediatric Type-1 Diabetes; A Case Study (Bangladesh Journal of Medical Science, 2020)
Diabetes mellitus is co-morbid with various metabolic and psychological disorders characterized by high blood glucose levels due to defects in insulin availability in body. Glucose work as a fuel to provide energy for all physical activities whereas in type 1 diabetes, the beta cells in the pancreas becomes unable to make insulin because of autoimmune disease, consequently there is no insulin to convert glucose leading to low energy level and other metabolic disorders. The disease is also called juvenile diabetes as usually starts to appear in childhood, that cannot be controlled but can be managed by timely diagnosis and care. The present study covers the case of a young child having type 1 diabetes in childhood and its consequences. The child inherited from paternal grandmother however other siblings were deficit. The case was become complicated because of poor timely investigations and management. Furthermore weak awareness and inappropriate healthcare practices made the disease more knotty. The work also covers the measures that should be taken by the health care providers through proper counseling and educating the parents and family, furthermore an accurate guidelines regarding nutrition, medications should be utmost. Self identification of having diabetes is necessary for school going children in order to manage abrupt hypoglycemic corollaries.Bangladesh Journal of Medical Science Vol.19(2) 2020 p.326-332